Self-tuning of PI speed controller gains using fuzzy logic controller - Nour, Mutasim; Bouketir, Omrane; Eng Yong, Ch’ng (Canadian Center of Science and Education, 2008)
The role of proportional-integral (PI) controller and proportional-integral-derivative (PID) controller as a speed controller for a Permanent Magnet Synchronous Motor (PMSM) in high performance drive system is still vital although new control techniques such as vector control theory that is more effective -but complex- is available. However, PI controller is slow in adapting to speed changes, load disturbances and parameters variations without continuous tuning of its gains. Conventional approach to these issues is to tune the gains manually by observing the output of the system. The tuning must be made on-line and automatic in order to avoid tedious task in manual control. Hence, an on-line self-tuning scheme using fuzzy logic controller (FLC) is proposed in this paper. The performance of the developed proposed controller is tested through a wide range of speeds as well as with load and parameters variations through simulation using MATLAB/SIMULINK. It is found that the proposed 25 rules FLC with adaptive input and output scaling factors enhances the performance of the system especially at high load inertia. The simulation results show that the developed controller can well adapt to speed changes as well as sudden speed reduction besides fast recovery from load torque and parameters variation and these show remarkable improvement compared to conventional PI controller performance.